Analisis Pemahaman Siswa Kelas III terhadap Materi Kalimat Aktif dan Pasif dengan Menggunakan LKPD di MI Ma’arif Mangunsari: Penelitian - Pratiwi, Ferica Intan; Royani, Miftahul Jannah; Wardani, Syifa Dian Putri; Himmah, Wulan Izzatul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the linguistic comprehension of third-grade students at MI Ma’arif Mangunsari concerning the distinction between active and passive sentence constructions through the integration of student worksheets (LKPD). Utilizing a qualitative descriptive design, data were obtained through systematic observation, semi-structured interviews, and analysis of students’ written responses. The results reveal that the LKPD facilitated learners’ grammatical awareness, with 75% of students demonstrating accurate identification of syntactic patterns in active and passive clauses. The contextual and interactive nature of the LKPD supported learners’ construction of linguistic meaning; however, difficulties persisted—particularly in recognizing the functional roles of subject and object as well as determining appropriate morphological adjustments in passive predicates. These findings indicate that learners’ syntactic and morphological competence is still emergent. The study affirms that LKPD can function both as a pedagogical tool and as a linguistic diagnostic instrument for mapping students’ comprehension. Further research is recommended to broaden the linguistic scope and participant diversity.